Architecture of Diplomacy: Chinese Construction Aid in Asia, 1950–1976. Issue 1 (16th April 2019) - Chang, Wei; Xue, Charlie; Ding, Guanghui
Construction aid was a physical tool – and indeed a key tactical manoeuvre – of international diplomacy that became especially obvious during the Cold War period. Among the outcomes of construction aid were cultural and technical exchanges between the donor and recipient countries. This essay examines the typical construction aid projects gifted by the Chinese Communist government and professionals to developing countries in Asia and African during the era of Chairman Mao Zedong, with a focus on key Asian examples. The remarkably high percentage of national income spent by Maoist China on construction aid might have increased the burden upon the lives of ordinary Chinese people, yet they gave Chinese architects rare opportunities to practice Modernism in overseas environments. The strength of the technical forces of the Chinese Communist state, and the wisdom of Chinese designers, were notably crystallized through a series of conference halls and stadiums built across Asia. These construction aid projects informed similar designs back in China, which led in turn to further innovations that could then again be exported abroad. Altogether it represents an important non-Western strand within Modernist architecture of the twentieth century.